(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
Social phobia (social anxiety disorder) is a severe anxiety disorder, that brings suffering and disabling. In this study, 17 patients with diagnosis of generalized social phobia were randomly allocated in two groups of treatments. One group received social skills training alone (SST) and the other group received the combination of social skills training and cognitive restructuring (SSTCR). Both treatments were effective, however the combination of techniques (SST-CR) proved to be significantly more effective than social skills training alone in the several measures instruments at the final of 8 weeks of treatment and at the 3-month follow-up.